EcoPharma@UCS 2024: a community-driven initiative for safe medication disposal and environmental stewardship / Nadia Jalaludin ... [et al.] - Jalaludin, Nadia; Abdullah, Zafirah Liyana; Husain, Noreen; Abdul Hamid, Hisyam; Hussin, Siti Nooraishah; Nordin, Massita (Faculty of Pharmacy, 2024)
As part of our continuous commitment to environmental safety and community well-being, the Safe Medication Disposal (SAFE-MEDd) team once again set out on a vital mission to address the frequently disregarded problem of appropriate and safe drug disposal. This year, we renamed our programme as ‘EcoPharma@UCS 2024’ as it involves participation from various bodies in the UiTM Cawangan Selangor (UCS) particularly the Puncak Alam Campus.